Evaluation of chronic gastritis with Helicobacter pylori using updated Sydney system - L., Anjana M.; Yevoor, Kavitha (International Journal of Research in Medical Sciences, 2021)
Background: Helicobacter pylori has been established as a major etiological factor in the pathogenesis of chronic gastritis. The aim of the study was to interpret the histopathological changes in chronic gastritis using updated Sydney system and the association with H. pylori infection. Methods: This was a 3 years study in which 62 gastric endoscopic mucosal biopsies taken from patients presenting with dyspepsia were included. Slides were stained with routine H and E and Giemsa for H. pylori detection in chronic gastritis cases. Grading of the variables were done with reference to Sydney system of classification. Results: Out of 62 gastric biopsy specimens, 55 cases (88.7%) were histopathological diagnosed as chronic gastritis. Among chronic gastritis, 21 (38%) cases showed H. pylori and majority of these being moderately (2+) positive. 27 (49%) cases showed neutrophilic activity with most of them showed mild (1+) activity. Chronic inflammation was seen 52 (94.5%) with majority of these graded as moderate (2+). Intestinal metaplasia was seen in 8 (14.5%) of cases with majority being mild (1+). Atrophy was seen only in 3 (5.4%) of cases with majority being mild (1+). Significant statistical association was found between H. pylori and neutrophilic activity (p<0.001). Conclusions: Histological evaluation of chronic gastritis using updated Sydney system of classification helps in detection of H. pylori infection and prevents further progression of the disease.